Weapon and tool use during the Nordic Bronze Age - Horn, Christian; Karck, Tine (Danish Journal of Archaeology, 2019)
The article is based on wear analysis carried out on 101 bladed objects including swords, spears, daggers, and knives. They are dating mostly to the Early Nordic Bronze Age. Wear marks vary over time and for each object category. The data are discussed to investigate the implications of the variation in the wear patterns. It is argued that a true specialization of the combat roles of swords and spears occurs first during the advanced Early Bronze Age. This may lead to the gradual loss of the role daggers had in combat. This is interpreted as evidence that the design and use of bladed objects inform each other and cause gradual changes.